Grupo operativo para hipertensos e diabéticos: resultados da interrupção das atividades devido a pandemia de COVID-19 - Adriano José de Figueiredo (2023)
Group process for hypertensive and diabetic patients: results of the interruption of activities due to the COVID-19 pandemic The COVID-19 pandemic, caused by SARS-CoV-2, has led to social isolation. This context demanded the interruption of collective actions in the so- called Primary Health Care (PHC) operative groups. This research aimed to analyze the contribution of the operative group for hypertensive and diabetic PHC patients in view of the interruption of group activities during the COVID-19 pandemic. This study was restricted to the geopolitical boundary of the municipality of Paraopeba/MG and included all users belonging to the territory of the UBS Papa João Paulo II, with a medical report of systemic arterial hypertension and type 2 diabetes mellitus, who regularly participated in the activities of an operative group for hypertensive/diabetic patients, between the period of 2018 to 2021. To carry out this research, a qualitative- quantitative approach was chosen. For the qualitative approach, an analysis was carried out based on documentary sources from the municipality and data from the IBGE, to characterize the municipality in terms of its social, environmental, economic and health aspects. To the characterization of the hypertensive and diabetic population participating to the Operative Group of UBS Papa João Paulo II and the activities carried out in the Operative Group, a descriptive analysis was carried out. To this analysis, we accessed documents and reports available in the city and in the UBS records, including the health status of hypertensive and diabetic patients and the performance of activities. The quantitative method was a retrospective longitudinal type, through the consultation and follow-up data on systolic and diastolic blood pressure, and capillary blood glucose. We accessed data from the municipal hypertensive patient’s passbook, the diabetics passbook and the physical and/or electronic medical records of citizens (PEC). Therefore, the sample consisted of 36 hypertensive individuals, who had their blood pressure levels monitored. The results obtained allowed verifying that the levels of systolic pressure increased significantly in the pandemic period, while the diastolic pressure remained stable. Despite this, both systolic and diastolic values were within the range considered as non-elevated pressure. Concerning the glycemic levels, there was no significant difference, but these remained high in the two compared periods. Therefore, the interruption of the regular activities of the operative group during the pandemic seems to have had an effect on the control of arterial hypertension and diabetes mellitus, given that there was no significant improvement in blood pressure and glucose levels. Indeed, the need to standardize the work of the hypertension/diabetes operative group was perceived, through planning, monitoring and evaluation of educational actions, with the purpose of guiding the participants' learning process towards the adequate management of their health problems.